2016
DOI: 10.1038/srep23378
|View full text |Cite
|
Sign up to set email alerts
|

NMR Observation of Mobile Protons in Proton-Implanted ZnO Nanorods

Abstract: The diffusion properties of H+ in ZnO nanorods are investigated before and after 20 MeV proton beam irradiation by using 1H nuclear magnetic resonance (NMR) spectroscopy. Herein, we unambiguously observe that the implanted protons occupy thermally unstable site of ZnO, giving rise to a narrow NMR line at 4.1 ppm. The activation barrier of the implanted protons was found to be 0.46 eV by means of the rotating-frame spin-lattice relaxation measurements, apparently being interstitial hydrogens. High-energy beam i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…25 Nevertheless, hydrogenation appears to have a direct influence on the ferromagnetism of ZnO nanoparticles, 27 single crystals, 28 thin films, 29 and nanostructures. 30 Theoretical studies have shown the possibility of a trigger magnetic order due to hydrogen adsorption on the surface of pure ZnO. 31,32 In this sense, experiments have been developed supporting the theoretical results and demonstrating the relationship between hydrogenation and surface magnetic response in pure ZnO films and nanoparticles, 27 together with evidence of the importance of OH-terminated surfaces.…”
Section: ■ Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…25 Nevertheless, hydrogenation appears to have a direct influence on the ferromagnetism of ZnO nanoparticles, 27 single crystals, 28 thin films, 29 and nanostructures. 30 Theoretical studies have shown the possibility of a trigger magnetic order due to hydrogen adsorption on the surface of pure ZnO. 31,32 In this sense, experiments have been developed supporting the theoretical results and demonstrating the relationship between hydrogenation and surface magnetic response in pure ZnO films and nanoparticles, 27 together with evidence of the importance of OH-terminated surfaces.…”
Section: ■ Introductionmentioning
confidence: 76%
“…Especially, the fact that it has been considered as a cause of the unintentional n-type conductivity presented by ZnO deserves attention. , Starting from van de Walle theoretical works, hydrogen impurities are suggested to have two kinds of donor-like states in ZnO: (i) interstitial hydrogen (H i ) at a bond center (H BC + ) or at an antibonding (H AB + ) site and (ii) substitutional H at an O site (H O ). , Through thermal annealing, the interstitial H can be easily removed due to its high mobility and thus H O is suggested to be a robust source for n-type conductivity . Nevertheless, hydrogenation appears to have a direct influence on the ferromagnetism of ZnO nanoparticles, single crystals, thin films, and nanostructures . Theoretical studies have shown the possibility of a trigger magnetic order due to hydrogen adsorption on the surface of pure ZnO. , In this sense, experiments have been developed supporting the theoretical results and demonstrating the relationship between hydrogenation and surface magnetic response in pure ZnO films and nanoparticles, together with evidence of the importance of OH-terminated surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the electrical properties of hydrogen-doped zinc oxide, several reported studies indicate doping of ZnO with hydrogen gives ferromagnetic properties to ZnO [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A través del tratamiento térmico el Hi puede eliminarse fácilmente debido a su alta movilidad (Wardle, Goss y Briddon, 2006), por lo que se sugiere que el HO es una fuente sólida para la conductividad de tipo-n (Janotti y Van De Walle, 2007). Sin embargo, la hidrogenación parece tener una influencia directa en el ferromagnetismo exhibido por nanopartículas (Yan et al 2016), monocristales (Khalid y Esquinazi, 2012), películas delgadas (Li et al 2011) y nanoestructuras de ZnO (Park et al 2016). Los estudios teóricos han demostrado la posibilidad de desencadenar ordenamiento magnético debido a la adsorción de hidrógeno en la superficie de ZnO puro , Liu et al 2009).…”
Section: Defectos En Znounclassified